Cytomegalovirus in immunosuppressed patients: a silent and potential killer. (2012)
Cytomegalovirus (CMV) is a recognized cause of morbidity and mortality among immunocompromised individuals. This review will concentrate on understanding the pathogenesis, clinical manifestations and laboratory diagnostic options for CMV infection.